PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE AUDITORIAL, INTELECTUALLY, REPETITION (AIR) UNTUK MENINGKATKAN PEMECAHAN MASALAH SISWA SMK KELAS XI - Retno Dwi Siswanto; Dadan Dadan; Padillah Akbar; Martin Bernard (Journal on Education, 2018)
The background of this research is the ability of solving the problem of mathematics of vocational high school students who are still relatively low, to improve this capability required research using cooperative learning method type AIR. The formulation of this research are: (1) How the application of cooperative learning model type AIR can improve problem solving a learning model AIR. Method of this research is classroom action research, to class student XI in one of the Vocational Schools in Sukabumi, which is 35 students. Instrument used is written test I - III, and nontest journal, observation sheet and questionnaire of attitude scale. The material in this research is Limit Function. The result of this research are: (1) the mathematical communication ability of students increases in line with the ongoing learning by using AIR type cooperative model, (2) Application of AIR type cooperative learning model can improve students' mathematical problem solving ability; (3) student activity in learning with using AIR type co-operative model obtained improvement, student's response to learning model of positive AIR type cooperative.